2003
DOI: 10.1094/pdis.2003.87.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Sweetpotato Virus Disease (SPVD): Distribution, Incidence, and Effect on Sweetpotato Yield in Peru

Abstract: Sweetpotato virus disease (SPVD), the most important disease affecting sweetpotato (Ipomoea batatas (L.) Lam), is caused by the synergistic interaction of the aphid-transmitted Sweetpotato feathery mottle virus (SPFMV) and whitefly-transmitted Sweetpotato chlorotic stunt virus (SPCSV). In this study, SPVD was the main disease in the Cañete Valley, the major sweetpotato-producing area in Peru. Studies on virus incidence showed that SPCSV and SPFMV were the most frequently identified viruses in Cañete Valley. Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 19 publications
2
73
1
7
Order By: Relevance
“…Milgram et al (1996) observed that whilst there was no significant effect of combined SPFMV and SPCSV on yield, a 30% yield reduction was observed for SPCSV in the second year. Gutierrez et al (2003) found a similar result in Peru; that SPFMV alone did not significantly affect yield, but in combination with SPCSV a significant yield reduction occurred.…”
Section: Sweetpotato Chlorotic Stunt Virus (Spcsv) Diseasesupporting
confidence: 55%
“…Milgram et al (1996) observed that whilst there was no significant effect of combined SPFMV and SPCSV on yield, a 30% yield reduction was observed for SPCSV in the second year. Gutierrez et al (2003) found a similar result in Peru; that SPFMV alone did not significantly affect yield, but in combination with SPCSV a significant yield reduction occurred.…”
Section: Sweetpotato Chlorotic Stunt Virus (Spcsv) Diseasesupporting
confidence: 55%
“…Presence and absence of viruses was identified in the field using biological property related to virus interaction with its host. Accordingly, severity and incidence of disease was recorded using the leaf and plant color and size deviation from normal appearance (purple, mosaic, vein clearing) and deformation of leaf size and shape to record virus-positive samples (Gutierrez et al, 2003). Severity was recorded using a 1-5 scale; where 1 = no visible symptoms, 2 = mild symptoms (a few local lesions on a few leaves), 3 = moderate symptoms (mosaic symptoms on leaves), 4 = severe symptoms (mosaic symptoms with plant stunting) and 5 = very severe symptoms of purpling/yellowing or mosaic on leaves, severe leaf distortion, reduced leaf size and severe stunting (Mwanga et al, 2013;Njeru et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…These include sweet potato chlorotic stunt virus (SPCSV), sweet potato feathery mottle virus (SPFMV), sweet potato mild mottle virus (SPMMV), sweet potato chlorotic fleck virus (SPCFV), sweet potato caulimo-like virus (SPCaLV), sweet potato mild speckling virus (SPMSV), C-6 (flexious rod virus), sweet potato latent virus (SwPLV), sweet potato virus G (SPVG) and cucumber mosaic virus (CMV) with SPFMV followed by SPCSV, SPVG and SPCSV being the most prevalent (Abraham, 2010;Tewodros et al, 2011;Shiferaw et al, 2014). In East Africa, SPVD can cause yield reduction up to 98% (Gibson et al, 1997;Gutierrez et al, 2003;Ndunguru et al, 2007).…”
Section: Sweet Potato (Ipomoea Batatas (L) Lam) Is One Of the World'mentioning
confidence: 99%
“…The incidences of virus diseases at both locations were evaluated using infection symptoms through visual assessment, on the leaves and other parts of the plants, from randomly selected three plants per plot. The development of purple color spots on the sample plants was used to identify virus-positive specimen (Gutierrez et al, 2003) as shown in Plate 1. The rooting characteristics of sweet potato are one of the main required parameter to evaluate the pest and drought resistance of this crop.…”
Section: Treatments and Experimental Designmentioning
confidence: 99%